Impact of Economic Globalization on Human Capital: Evidence from Nigerian Economy - Solarin, Sakiru Adebola; Eric, Olabisi Olabode (International Journal of Economics and Financial Issues, 2015)
Investment in human capital in relation to global world is to achieve an optimum return in terms of a gainful employment, productivity and high standard of living. This paper uses Autoregressive Distributed Lag (ARDL) model to determine the cointegration, long run and short run elasticities among human capital, economic growth, economic globalization and foreign direct investment (FDI), for the period 1980-2011. The empirical results reveal that there is a long run relationship among the variables tested in this study. Also, economic growth and FDI show a positive impact on human capital and economic globalization indicates a negative impact on human capital in Nigeria. Keywords: Human Capital; Economic Globalization; ARDL; Nigeria JEL Classifications: F02; F66; J24; J61